Pengaruh Kualitas Jasa terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan sebagai Variabel Intervening di Kota Palembang - Nargis, Lusia (Universitas Muhammadiyah Palembang, 2017)
ABSTRACTPurpose - The purpose of this research are to know influence of service quality ( tangibles, reliability, responsiveness,assurance and emphaty) to customer satisfaction, trust and customer loyalty Bus Rapid Transit (BRT) Trans Musi in Palembang and also influence customer satisfaction and trust to customer loyalty Bus Rapit Transit (BRT)inj PalembangDesign/methodology - This research is taken 100 passengers BRT- Trans Musi, while data is collected by using questionnaire. Analysis technique use Path Analysis and processed using sofware SPSS 22,0 for windowsFindings – This results shows there are significant correlations between service quality to customer loyalty in the dimensions of service quality is tangibles, reliability, responsiveness, assurance and empathy. The fifth aspect of this dimension of service quality has a positive influence on the level of customer loyalty 81,7 percent, and there is significant correlations between customer satisfactions and trust to customer loyalty 6,56 percent, service quality has a positif influence on customer satisfaction 37,5 percent, In direct, service quality influence customer service trust and customer loyalty 90,8 percent